Product Innovation and Transportation Technology in a Cournot Duopoly - Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
In this paper I will evaluate the strategic behavior of two firms which can activate R&D investments either to process or to product innovation. I will consider a particular kind of process R&D activity, which I will call Transport and Communication R&D and which aims at increasing the net amount of the product that reaches consumers. I will limit my study to a Cournot duopoly setting. The strategic interaction will be therefre axpressed in terms of a two-stage three strategy game, where firms first decide whether to invest in one of the two types of R&D and then they compete in the market by setting quantities. As a result, I will obtain both symmetric and asymmetric equilibria, depending on the relative efficiency of the R&D effert.
Keywords: 330